Biochemical parameters of blood of first-calf cows - Kosilov, V. I.; Kadralieva, B. T. (Жәңгір хан атындағы БҚАТУ, 2024)
The article presents the results of studies of morphological parameters of blood, mineral and protein composition in the blood serum of first-calf cows. The effect of the genotype on both the number of red blood cells and the hemoglobin content in the blood has been established. The minimum value of the analyzed indicators was distinguished by the first-calf cows of the black-andwhite breed. They were inferior to the Holstein peers of the German selection in terms of the number of red blood cells in the blood in winter by 0.33 · 1012/l, in summer – by 0.45 · 1012/l; according to the hemoglobin content – by 2.47 g/l and 2.95 g/l, respectively, Dutch holsteins – by 0.46 ·1012/l and 0.68 · 1012/l, 3.42 g/l and 3.25 g/l, crossbreeds ½ holsteins of German selection × ½ black-and-white – 0,18· 1012/ l and 0.09 · 1012/l, 1.40 g/l and 1.92 g/l, crossbreeds ½ holstein Dutch selection × ½ black and mottled – 0,24 · 1012/ l and 0.32 · 1012/l, 2.16 g/l and 2.40 g/l. The effect of the genotype on the albumin content in the blood serum of first-calf cows has been established. At the same time, their maximum level was distinguished by animals of the Holstein breed of foreign selection of groups II and III, the purebred first–born cows of the black–and-white breed of group I, crossbreeds of groups IV and V were characterized by intermediate inheritance of the trait.
Ғылым және білім: Ғылым, зерттеулер, білім: даму тенденциялары: акад. Қ. И. Сәтбаевтың 125 жылдығына арналған халықаралық ғылыми-практ. конф. материалдар жинағы (12 сәуір 2024 ж.) = Наука и образование: Наука, исследования, образование: тенденции развития: сб. мат. междунар. науч.-практ. конф. посвящ. 125-летию акад. К. И. Сатпаева (12 апреля 2024 г.) = Science and education: Science, research, education: development trends: unternational scientific and practical conf. dedicated to the 125th anniversary of acad. K. I. Satpayev (12 april 2024). - Орал: Жәңгір хан атындағы БҚАТУ. - 2024. - № 2 (75) : қосымша № 1. - Р. 179-186
Keywords: leukocytes; black-and-white breed; holsteins of German and Dutch breeding; morphological composition of blood; erythrocytes; vitamin A; dairy cattle breeding; научный журнал; конференции